Impact of Infodemic on Public Perception on Covid-19 Pandemic: Web-Based Cross-Sectional Survey: Pharmaceutical Science-Pharmacy Practice - Sahithi, Bogireddy; Sharon, K.; Reddy, M.V. Rahul; Bhargav, B.Pranav; Narayana, Dr. G. (International Journal of Life Science and Pharma Research, 2022)
Infodemic’ (an overabundance of information) that makes it tough for people to find responsible sources and reliable guidance when they need it. This generates a need to know whether the public are able to distinguish fake news from true ones and the information sources used. The study aims to determine the impact of infodemic on public perception of health during the COVID- 19 pandemic and to assess its impact on the psychological well-being of the public. An online web based cross sectional study was conducted among people who were aged above 15 years. The data was collected through online mode by providing google links to fill the validated questionnaire form through various social media platforms. The questionnaire consists of demographic details, knowledge and practice related questions. The data was analyzed using Chi-square test. A total of 715 responses were considered for analysis in which the majority of the age group belongs to 18- 24 years and mostly living in urban (44%) and rural (41%). Information Sources mostly used include Internet (630), Mobile phone usage (630), and TV (530). Standard (or) Trusted sources according to people were Government websites (407). It was observed that most people have good knowledge about COVID-19 prevention and were practicing the safety measures. The study concludes that availability of abundance of information sources and lack of awareness on how to crosscheck made people to follow some activities in the view of protection without knowing the truth. This impact of infodemic can be controlled by health care professionals including pharmacists by giving updated and evidence-based scientific advice on reliable COVID- 19 information to their communities via flyers and multimedia.